Dupilumab provides rapid and sustained improvement in SCORAD outcomes in adults with moderate-to-severe atopic dermatitis: combined results of four randomized phase 3 trials. (2nd January 2022) - Barbarot, S.; Wollenberg, A.; Silverberg, J. I.; Deleuran, M.; Pellacani, G.; Armario-Hita, J. C.; Chen, Z.; Shumel, B.; Eckert, L.; Gadkari, A.; Lu, Y.; Rossi, A. B.
Abstract: Background: Dupilumab, a first-in-class therapy targeting the two key cytokines involved in the persistent underlying inflammatory pathway in atopic dermatitis (AD), is approved for treatment of moderate-to-severe AD in Europe, USA, Japan and several other countries. Objective: To assess dupilumab effects on SCORing Atopic Dermatitis (SCORAD) and component scores (objective and subjective SCORAD) over time in adults with moderate-to-severe AD. Methods: This post hoc analysis included 2, 444 patients in four placebo-controlled, double-blind, randomized, phase 3 trials. SOLO 1 and 2 (NCT02277743; NCT02277769) evaluated 16 weeks of dupilumab monotherapy against placebo. CAFÉ (NCT02755649) and CHRONOS (NCT02260986) evaluated dupilumab with concomitant topical corticosteroids (TCS) against TCS alone for 16 and 52 weeks, respectively. Results: 2, 444 patients randomized to treatment in SOLO 1 and 2 ( N = 1, 379), CAFÉ ( N = 325) and CHRONOS ( N = 740) were analyzed. Dupilumab treatment significantly improved overall SCORAD and individual components as early as Week 1 or 2, with significant and clinically meaningful differences vs. control through end of treatment ( p < .0001). These results occurred irrespective of dupilumab regimen, 300 mg subcutaneously weekly or every 2 weeks. Conclusions: In four large phase 3 trials in adults with moderate-to-severe AD, dupilumab treatment with or without concomitant TCS resulted in rapid and sustained improvements in all SCORAD outcomes vs. placebo or TCS alone.